Development and protection evaluation of two new, advanced ceramic composite thermal spray coatings, Al2O3-40TiO2 and Cr3C2-20NiCr on carbon steel petroleum oil piping - Zavareh, M.A.; Sarhan, A.A.D.; Zavareh, P.A.; Bushroa, A.R.; Basirun, Wan Jefrey; Ismail, M.C. (Elsevier, 2016)
Carbon steel is the most commonly used material in the petroleum industry owing to its high performance and relatively low cost compared with highly alloyed materials. The corrosion resistance of carbon steel in aqueous solutions is dependent on the surface layer created on carbon steel. This layer often consists of siderite (FeCO3) and cementite (Fe3C), but it is neither compact nor dense. To improve the carbon steel surface resistance against corrosion and wear, a compact and dense layer can be deposited onto the surface by thermal spray coating. In this research, Al2O3-40TiO2 and Cr3C2-20NiCr were deposited onto mechanical part surfaces by HVOF spray technique. The present study describes and compares the electrochemical behavior of carbon steel, Cr3C2-20NiCr and Al2O3-40TiO2 in 3.5% NaCl using open-circuit potential measurement (OCP) and electrochemical impedance microscopy (EIS) for 36 days. The tribological and mechanical properties are also investigated using a tribometer (pin-on-disc). The results indicate that these chemical composition coatings facilitated significant anti-corrosion and anti-wear improvement. However, the samples coated with Al2O3-40TiO2 exhibited the lowest corrosion rate. In terms of wear performance, both coated samples displayed similar behavior under different loads. Scanning electron microscopy (SEM) showed the distinctive microstructure of the HVOF-sprayed samples before and after corrosion and wear testing.